Macrophage Markers Do Not Add to the Prediction of Liver Fibrosis by Transient Elastography in Patients With Metabolic Associated Fatty Liver Disease - Kazankov, Konstantin; Rosso, Chiara; Younes, Ramy; Armandi, Angelo; Hagström, Hannes; Møller, Holger Jon; Stål, Per; Bugianesi, Elisabetta; Grønbæk, Henning (Frontiers in Medicine, 2020)
Background and Aims: Non-invasive fibrosis staging is essential in metabolic associated fatty liver disease (MAFLD). Transient elastography (TE) is a well-established method for liver fibrosis assessment. We have previously shown that the macrophage marker sCD163 is an independent predictor for fibrosis in MAFLD. In the present study we tested whether the combination of macrophage markers and TE improves fibrosis prediction. Methods: We measured macrophage markers soluble (s)CD163 and mannose receptor (sMR) in two independent cohorts from Italy (n = 141) and Sweden (n = 70) with biopsy-proven MAFLD and available TE. Results: In the Italian cohort, TE and sCD163 showed similar moderate associations with liver fibrosis (rho = 0.56, p < 0.001 and rho = 0.42, p < 0.001, respectively). TE had an area under the Receiver Operating Characteristics curve (AUROC, with 95% CI) for fibrosis; F ≥ 2 = 0.79 (0.72–0.86), F ≥ 3 = 0.81 (0.73–0.89), F4 = 0.95 (0.90–1.0). sCD163 also predicted fibrosis well [F ≥ 2 = 0.71 (0.63–0.80), F ≥ 3 = 0.82 (0.74–0.90), F4 = 0.89 (0.76–1.0)]. However, combining sCD163 and TE did not improve the AUROCs significantly [F ≥ 2 = 0.79 (0.72–0.86), F ≥ 3 = 0.85 (0.78–0.92), F4 = 0.97 (0.93–1.0)]. In the Swedish cohort, TE showed a closer association with fibrosis (rho = 0.73, p < 0.001) than sCD163 (rho = 0.43, p < 0.001) and sMR (rho = 0.46, p < 0.001). TE predicted fibrosis well [F ≥ 2 = 0.88 (0.80–0.97), F ≥ 3 = 0.90 (0.83–0.97), F4 = 0.87 (0.78–0.96)], whereas sCD163 did not (best AUROC 0.75). sMR showed a better prediction [F ≥ 2 = 0.68 (0.56–0.81), F ≥ 3 = 0.82 (0.71–0.92), F4 = 0.79 (0.66–0.93)], but the addition of sMR did not further improve the prediction of fibrosis by TE. Conclusion: In these cohorts of MAFLD patients, TE was superior to macrophage markers for fibrosis prediction and in contrast to our hypothesis the addition of these markers to TE did not improve its predictive capability.